New Insights Emerging from Recent Investigations on Human Group II Pyridoxal 5’-Phosphate Decarboxylases - Paiardini, Alessandro; Giardina, Giorgio; Rossignoli, Giada; Borri Voltattorni, Carla; Bertoldi, Mariarita (Current Medicinal Chemistry, 2017)
Aromatic amino acid, cysteine sulfinic acid, glutamate and histidine decarboxylases, belonging to group II of pyridoxal 5'-phosphate-dependent enzymes, catalyze the synthesis of dopamine/serotonin, hypotaurine, γ-aminobutyric acid and histamine, respectively. Considering that these reaction products are all essential bioactive molecules, group II decarboxylases have been long studied from an evolutionary, biochemical and pharmacological standpoint. Despite the fact that they all belong to a common fold-type, during evolution each decarboxylase has evolved unique structural elements responsible for its substrate specificity. Combining a literature update with bioinformatic analyses, this review focuses on some structural determinants shared by these enzymes revealing their intrinsic substrate specificity and highlighting the importance of some residues/regions for catalytic competence. In particular, two key structural features emerge: 1) a mobile catalytic loop, and 2) an open-to-close conformation accompanying the apo-holo transition. Drawing attention on these elements is crucial in correlating subtle structural modifications to functional properties for the understanding, at a molecular level of a pathological condition. This is corroborated by the increasingly important role played by these decarboxylases in several different pathological states (autoimmune diseases, type I diabetes, Parkinson's disease, aromatic amino acid decarboxylase deficiency, Tourette's syndrome and cholangiocarcinoma).
Keywords: Pyridoxal 5' -phosphate